ACM Symposium on Applied Perception 2020 2020
DOI: 10.1145/3385955.3407927
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating the Perception of Visual Roughness into the Design of Mid-Air Haptic Textures

Abstract: Ultrasonic mid-air haptic feedback enables the tactile exploration of virtual objects in digital environments. However, an object's shape and texture is perceived multimodally, commencing before tactile contact is made. Visual cues, such as the spatial distribution of surface elements, play a critical first step in forming an expectation of how a texture should feel. When rendering surface texture virtually, its verisimilitude is dependent on whether these visually inferred prior expectations are experienced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…To provide a tactile sensation in midair, ultrasonic phased arrays composed of several speakers (see Figure 1c) can be computer-controlled to emit focused ultrasound over distance (e.g., 20 cm) and enable a person to perceive tactile sensations in mid-air without the need of physical attachments, such as a glove. These tactile sensations can be single or multiple focal points on the hand, 3D shapes (Carter et al, 2013), or textures (Beattie et al, 2020). This unique combination is enabling novel interaction paradigms previously only seen in science fiction movies.…”
Section: From Physical To Contactless Tactile Stimulationmentioning
confidence: 99%
“…To provide a tactile sensation in midair, ultrasonic phased arrays composed of several speakers (see Figure 1c) can be computer-controlled to emit focused ultrasound over distance (e.g., 20 cm) and enable a person to perceive tactile sensations in mid-air without the need of physical attachments, such as a glove. These tactile sensations can be single or multiple focal points on the hand, 3D shapes (Carter et al, 2013), or textures (Beattie et al, 2020). This unique combination is enabling novel interaction paradigms previously only seen in science fiction movies.…”
Section: From Physical To Contactless Tactile Stimulationmentioning
confidence: 99%
“…Freeman et al [12] rendered geometric features at the intersection between the hand and a complex surface as a crude representation of macro-texture elements. Beattie et al [3,4] showed a more nuanced approach to texture generation, extracting features from images and rendering them dynamically in response to hand movement.…”
Section: Background 21 Ultrasound Haptic Feedbackmentioning
confidence: 99%
“…A key characteristic in surface roughness is the physical size and separation of physical elements: macrotexture and micro-texture elements being greater, and less than, 0.2 mm respectively [27]. We point readers towards work by Klatzky and Lederman [27], who discuss texture perception in detail, and Beattie et al [3], who interpret the literature on roughness with a focus on ultrasound haptic perception. The latter is particularly relevant to this paper, since ultrasound haptic stimuli lack the physical elements that contribute to typical roughness perception.…”
Section: Roughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 2D texture feature extraction and analysis method of color images is combined to analyze the texture feature of color images, improve the image quality and detection ability of color images, study the 2D texture recognition method of color images, and improve the accurate analysis and 3D feature resolution ability of color multitexture image. In [5], the authors used a combination of macro-and local aspects to obtain multiscale data information for building an image information model. e authors in [6] put forward a method of image segmentation based on the induction and application of multifeature information in remote sensing images.…”
Section: Introductionmentioning
confidence: 99%